Comparison of the carotenoid profiles of commonly consumed smear-ripened cheeses. (January 2021) - Yeluri Jonnala, Bhagya R.; McSweeney, Paul L.H.; Cotter, Paul D.; Zhong, Siqiong; Sheehan, Jeremiah J.; Kopec, Rachel E.
Abstract: The objective of this study was to identify the carotenoids imparting the orange colour to the rind, and pale yellow color to the core, of selected smear-ripened cheeses. The cheeses investigated were Charloe, Ashbrook, Taleggio, and Limburger, and were sourced from artisanal markets. Samples of the rind and core were extracted using non-polar solvents, followed by saponification to hydrolyze triglycerides to remove fatty acids, and to release carotenoid esters. Extracts were tested using ultra-high pressure liquid chromatograph-diode array detector-high resolution mass spectrometry (UHPLC-DAD-MS and -MS/MS), and identities of α- and β-carotene, lycopene, and β-cryptoxanthin confirmed with authentic standards. β-Carotene was the predominant species in both the rind and core, absorbing 80% of the signal at 450 nm in all cheese extracts tested, as well as minor quantities of β-cryptoxanthin and α-carotene. Carotenoids unique to the rind included lycopene as well as the rare bacterial carotenoids previously identified in bacterial isolates of cheeses (i.e. decaprenoxanthin, sarcinaxanthin, and echinenone). This is the first detailed characterisation of carotenoids extracted directly from smear-ripened cheeses, and reveals that smear-ripened cheese can contribute both provitamin A carotenoids as well as C50 carotenoids to the human diet. Highlights: Carotenoids from four smear-ripened cheeses were extracted and profiled. Provitamin A carotenoids predominated in both rind and core samples. Lycopene and C50 bacterial carotenoids were unique to rind samples. Similar carotenoids profiles were observed between all smear-ripened cheeses tested.